Effect of concentration and duration of particulate matter exposure on the transcriptome and DNA methylome of bronchial epithelial cells. Issue 1 (28th February 2021) - Huang, Steven K; Tripathi, Priya; Koneva, Lada A; Cavalcante, Raymond G; Craig, Nathan; Scruggs, Anne M; Sartor, Maureen A; Deng, Furong; Chen, Yahong
Abstract: Exposure to particulate matter (PM) from ambient air pollution is a well-known risk factor for many lung diseases, but the mechanism(s) for this is not completely understood. Bronchial epithelial cells, which line the airway of the respiratory tract, undergo genome-wide level changes in gene expression and DNA methylation particularly when exposed to fine (<2.5 µm) PM (PM2.5 ). Although some of these changes have been reported in other studies, a comparison of how different concentrations and duration of exposure affect both the gene transcriptome and DNA methylome has not been done. Here, we exposed BEAS-2B, a bronchial epithelial cell line, to different concentrations of PM2.5, and compared how single or repeated doses of PM2.5 affect both the transcriptome and methylome of cells. Widespread changes in gene expression occurred after cells were exposed to a single treatment of high-concentration (30 µg/cm 2 ) PM2.5 for 24 h. These genes were enriched in pathways regulating cytokine–cytokine interactions, Mitogen-Activated Protein Kinase (MAPK) signaling, PI3K-Akt signaling, IL6, and P53. DNA methylomic analysis showed that nearly half of the differentially expressed genes were found to also have DNA methylation changes, with just a slightly greater trend toward overall hypomethylation across the genome. Cells exposed to a lower concentration (1 µg/cm 2 ) of PM2.5 demonstrated a comparable, but more attenuated change in gene expression compared to cells exposed to higher concentrations. There were also many genes affected by lower concentrations of PM2.5, but not higher concentrations. Additionally, repeated exposure to PM2.5 (1 µg/cm 2 ) for seven days resulted in transcriptomic and DNA methylomic changes that were distinct from cells treated with PM2.5 for only one day. Compared to single exposure, repeated exposure to PM2.5 caused a more notable degree of hypomethylation across the genome, though certain genes and regions demonstrated increased DNA methylation. The overall increase in hypomethylation, especially with repeated exposure to PM2.5, was associated with an increase in expression of ten–eleven translocation enzymes. These data demonstrate how variations in concentration and duration of PM2.5 exposure induce distinct differences in the transcriptomic and DNA methylomic profile of bronchial epithelial cells, which may have important implications in the development of both acute and chronic lung disease.